2017
DOI: 10.1177/1745499917712610
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of American, Japanese, and Taiwanese early childhood teachers’ perceptions of clean-up time

Abstract: The purpose of this study was to examine similarities and differences of American, Japanese, and Taiwanese kindergarten teachers’ perspectives about clean-up time. The participants consisted of two female American kindergarten teachers in the southeastern US, two female Japanese kindergarten teachers on the main island, and two female Taiwanese kindergarten teachers from central Taiwan, all of whom teach four-year-olds. Qualitative analysis of the data yielded four themes regarding teachers’ views of clean-up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Preschool teachers in Japan, United States, and Taiwan looked on activity cleaning up through collaboration and participation direct children can increase knowledge and skills as well as need for study cleanliness. By individual this can using video and reflecting understanding early childhood about what are they doing [17].…”
Section: " (P1) "Clean and Healthy Life Skills Are Very Important And...mentioning
confidence: 99%
“…Preschool teachers in Japan, United States, and Taiwan looked on activity cleaning up through collaboration and participation direct children can increase knowledge and skills as well as need for study cleanliness. By individual this can using video and reflecting understanding early childhood about what are they doing [17].…”
Section: " (P1) "Clean and Healthy Life Skills Are Very Important And...mentioning
confidence: 99%
“…In many classrooms, many teachers often use different kinds of cues for tidy-up time, and simply giving children two signals before a transition could help with this activity (Thelen and Klifman, 2011; Weldemariam, 2014). Some studies found that saving children’s play activities can promote smooth transitions to other activities (Izumi-Taylor et al, 2015; 2017; Weldemariam, 2014).…”
mentioning
confidence: 99%